1992
DOI: 10.1891/0889-8391.6.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ Memories for Therapeutic Events and Ratings of Session Effectiveness

Abstract: We investigated various relationships between therapists’ and clients’ memories for important therapeutic events and their assessments of the effectiveness of therapy sessions in 11 therapy dyads. Results showed that clients had greater accuracy of recall of important events for sessions they rated as more effective. There was also a greater match between therapists and clients in their choice of important events for more effective sessions. Finally, therapists displayed greater overall accuracy of recall than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
4

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 0 publications
5
31
4
Order By: Relevance
“…Elliott, 1983; Llewelyn, 1988). Cummings, Martin, Hallberg, and Slemon (1992) also found that counsellors were more specific in their recalls. They suggested that likelihood of match between the counsellors' and clients' perspective increased if the counsellors rated the working alliance higher.…”
Section: Summary Of Findingsmentioning
confidence: 86%
See 1 more Smart Citation
“…Elliott, 1983; Llewelyn, 1988). Cummings, Martin, Hallberg, and Slemon (1992) also found that counsellors were more specific in their recalls. They suggested that likelihood of match between the counsellors' and clients' perspective increased if the counsellors rated the working alliance higher.…”
Section: Summary Of Findingsmentioning
confidence: 86%
“…The findings which show that the match between the clients' and the therapists' perspectives increases with a good outcome and with a good relationship (e.g., Cummings, Martin, et al , 1992; Kivlighan & Arthur, 2000) suggests that in successful therapy the therapists may be more attuned to the clients' ongoing experience of therapy. Whether it is down to the skilfulness of therapists or it is just a natural phenomenon of a good ‘flow’ between the therapist and the client (cf.…”
Section: Discussionmentioning
confidence: 99%
“…There is now a growing body of research suggesting that perspective congruence is a meaningful contributor to outcome. For example, more agreement between clients and therapists in their recall of important session events has been found to be relate to session effectiveness (Cummings et al, 1992) as well as to final outcome (Kivlighan & Arthur, 2000). More recently, in two studies using response surface analysis, Marmarosh and Kivlighan (2012) found that as the therapist and client had more positive agreement on the perceived alliance at the beginning of the treatment, clients experienced greater symptom change.…”
mentioning
confidence: 99%
“…There are some things we should decide, such as what are the goals of these meetings as far as you are concerned. Another guideline for initiating the discussion on termination is that the termination dialogue should be tailored to the individual patient–therapist dyad. Every dyad has its own way of interacting and uses its own “emotional language.” Metaphors (Cummings, Hallberg, Slemon, & Martin, 1992) that are taken from treatment narrative make the conversation on termination easier; the therapist should use terms from the patient’s familiar world. For example, if the patient is an architect, the therapist can use terms related to building and can talk about the foundations needed to create what they built together.…”
Section: How To Initiate or Engage In The Discussion Of Psychotherapy...mentioning
confidence: 99%
“…Although the therapeutic guidelines we proposed have not been directly examined, some of the interventions they include have received empirical support. With respect to initiating the discussion on termination, the use of metaphors (Cummings et al, 1992) has been found to lead to treatment success. With respect to the termination process, an empirical meta-analysis stresses the importance of rupture resolution processes to successful treatment (Eubanks et al, 2018).…”
Section: Research Supports the Suggested Interventionsmentioning
confidence: 99%